War, State Formation and National Identity on the Fringes of the Atlantic World - Ó Néill, Eoin (ABEI Journal, 2007)
This article looks at the relationship between war, state formation and national identity in England and Ireland. Focusing on the Elizabethan andStuart periods, I show how English rule was extended over Ireland in a series of wars. As well as ending the possibility of the development of an alternative type of state in Ireland, where a centralised colonial state emerged instead, this also had a profound impact on state formation in Britain. In addition, this process also contributed to a new type of national identity in both countries, which was geographically restricted and based on religion.